What Motivates You to Exercise? Phenomenology of Long-Term Physical Activity Practice - Tavernier Morga, Maria Eugenia (2021)
Objective. To know the experience of long-term active people to understand their relationship with physical practice in three stages: beginning of active life, current motivation, and facing barriers. Method. A phenomenological analysis was done on in-depth interviews. N = 11 adults have been active at a sufficient level for, at least, the last 10 years. Results. Four categories were found: the autonomous experience, the decision making, the preference for an active life acquired since childhood, and the habit through which they regulate their emotions. As a conclusion, the characteristics of the experience of active people with physical activity confirmed aspects about self-determined motivation. Useful elements are suggested in the intervention aimed at long-term activation.ivation.